015 Prevalence, pattern and significance of late gadolinium enhancement in a healthy asymptomatic cohort. (5th May 2016) - Weir-McCall, Jonathan R; Fitzgerald, Kerrie; Papagiorcopulo, C; Gandy, Stephen J; Lambert, Matthew; Belch, Jill JF; Cavin, Ian; Littleford, Roberta; MacFarlane, Jennifer A; Matthew, Shona Z; Nicholas, R Stephen; Struthers, Allan D; et al.
Abstract : Introduction: Unrecognised myocardial infarctions (UMIs) have been described in 19–30% of the population using late gadolinium enhancement (LGE). However these studies have focussed on unselected cohorts including those with known cardiovascular disease. The aim of the current study was to ascertain the prevalence of UMIs in a non-high risk population and their physiological significance. Methods: 5, 000 volunteers >40 years with no history of cardiovascular disease (CVD) and a 10 year risk of CVD of less than 20% were recruited to the Tayside Screening for Cardiac Events (TASCFORCE) study. Those with a BNP level greater than their gender-specific median were invited for a whole-body MR angiogram and cardiac MR including LGE. LGE was classed as absent, UMI, or non-specific. Results: 1, 529 completed the imaging study with 53 (3.6%) excluded due to missing data or inadequate LGE image quality. 10 of the remaining 1476 (0.67%) displayed LGE. Of these, 3 (0.2%) were consistent with UMI, while 7 were non-specific occurring in the mid-myocardium (n = 4), epicardium (n = 1) or right ventricular insertion points (n = 2). Those with UMI had significantly higher BNP(median 116 (range 31–133) vs 22.6 (5–175) pg/ml, p = 0.015), lower ejection fraction (54.6 (36–62) vs 68.9 (38–89) %, p = 0.007) and larger end systolic volume (36.3 (27–61) vs 21.7 (5–65) ml/m 2, p = 0.014). Those with non-specific LGE had lower diastolic blood pressure (68 (54–70) vs 72 (46–98) mmHg, p = 0.013), but no differences in their cardiac function. Conclusion: Despite previous reports describing high prevalence of UMI, those who are of low-intermediate cardiovascular risk have a very low prevalence of UMI. LGE typical of UMI is associated with significantly impaired cardiac function, while LGE atypical of UMI has no adverse effect on function.